Molecular Brightness Approach for FRET Analysis of Donor-Linker-Acceptor Constructs at the Single Molecule Level: A Concept - Kay, Taryn M.; Aplin, Cody P.; Simonet, Rowan; Beenken, Julie; Miller, Robert C.; Libal, Christin; Boersma, Arnold J.; Sheets, Erin D.; Heikal, Ahmed A. (Frontiers in Molecular Biosciences, 2021)
In this report, we have developed a simple approach using single-detector fluorescence autocorrelation spectroscopy (FCS) to investigate the Förster resonance energy transfer (FRET) of genetically encoded, freely diffusing crTC2.1 (mTurquoise2.1–linker–mCitrine) at the single molecule level. We hypothesize that the molecular brightness of the freely diffusing donor (mTurquoise2.1) in the presence of the acceptor (mCitrine) is lower than that of the donor alone due to FRET. To test this hypothesis, the fluorescence fluctuation signal and number of molecules of freely diffusing construct were measured using FCS to calculate the molecular brightness of the donor, excited at 405 nm and detected at 475/50 nm, in the presence and absence of the acceptor. Our results indicate that the molecular brightness of cleaved crTC2.1 in a buffer is larger than that of the intact counterpart under 405-nm excitation. The energy transfer efficiency at the single molecule level is larger and more spread in values as compared with the ensemble-averaging time-resolved fluorescence measurements. In contrast, the molecular brightness of the intact crTC2.1, under 488-nm excitation of the acceptor (531/40 nm detection), is the same or slightly larger than that of the cleaved counterpart. These FCS-FRET measurements on freely diffusion donor-acceptor pairs are independent of the precise time constants associated with autocorrelation curves due to the presence of potential photophysical processes. Ultimately, when used in living cells, the proposed approach would only require a low expression level of these genetically encoded constructs, helping to limit potential interference with the cell machinery.